Behavioral aspects of the parasite Cotesia flavipes produced in a laboratory on the north coast of Paraíba (Research, Society and Development, 2021)
Among the multiple aspects that permeate the biological and sustainable control in the sugarcane (Saccharum officinarum) culture, this study focus on the behavioral aspects of the laboratory-produced Cotesia flavipes in the north coast of Paraíba, more precisely in the city of Mamanguape, with the purpose to evaluate the laboratory produced behavior for better field performance. The experiments were carried out at the Mass Production of Biological Control Laboratory (MPBCL) of the Paraíba Sugarcane Growers Association (PSGA) and performed in a completely randomized design, in rooms with a controlled Temperature of 21, 25 and 29 ºC, relative air humidity ranging from 70±10% and 12 hours photophase. 34 Caterpillars (repetition) were used for each temperature, evaluating the following biological variables: egg-larva duration; pupae duration; adults; number of cocoons per caterpillar; pupae viability; sex ratio at the three temperatures and efficiency among male and female manipulators. The results obtained in the research emphasize that the behavioral aspects of laboratory-produced parasitoids present difference among the controlled temperatures. It is inferred that the parasitoid sample presents acceptable standards for the analyzed parameters.